(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In India, 78.9% of births take place in hospitals, yet only 42.6% of new mother’s start nursing within an hour after giving birth, according to the National Family Health Survey- 4 (Mary et al., 2022). to determine the factors that contribute to new mothers' delayed breastfeeding start and to estimate the percentage of new mothers who begin breastfeeding early upon discharge from a tertiary care hospital. One hundred mothers participated in this analytical cross-sectional research conducted at a hospital. On the day after release, we conducted interviews with the mothers following informed permission and clearance from the hospital Review Board. With Graph Pad, multivariate logistic regression was carried out. The interquartile range for breastfeeding beginning was 30 to 180 minutes, with a median of 90 minutes. EIBF was used by 40% of the mothers overall, whereas exclusive breastfeeding was used by 60%. Extended recuperation following spinal anesthetic, mother lethargy, a lack of awareness regarding the significance of colostrum, and discomfort from the post-cesarean position were among the factors contributing to nursing delays. The multivariate analysis revealed that mothers' inadequate breastfeeding knowledge (36%; P=0.010) and cesarean section delivery (58%; P=0.005) were the main causes of the delay in breastfeeding beginning, whereas 16% had other minor reasons. Therefore, it is essential to enhance nursing and nutritional advice for expectant moms as well as the training of medical staff to support EIBF, especially in cases like cesarean sections.